Visual presentation of research results: IITA research guide, No. 45 - Zachmann, R.; Siri, C. (1998)
Well prepared visual aids improve communication of research results and enhance the impact of your presentation. Your research will be more appreciated. However, poor visual aids ruin even the best message. You can spoil a presentation by presenting badly prepared visual aids, or by presenting visual aids badly. This Research Guide summarizes recommendations on how to plan, prepare, and deliver visual presentation of research results. It concentrates on visual aids containing text, tables, and graphics. The Research Guide does not cover photography.